Sponge City Policy and Sustainable City Development: The Case of Shenzhen - Wang, Ye; Jiang, Zhe; Zhang, Lin (Frontiers in Environmental Science, 2022)
The massive construction of buildings has changed the city's aquatic ecological environment. The aquatic ecological condition of the city has been deteriorated, with serious water issues. In order to coordinate various departments to jointly build the sponge city and improve water environment, Shenzhen Government formulated the policy note on "Interim Measures for the Construction Management of Shenzhen Sponge City". This article discusses the impact of the policy note on Shenzhen's construction of sponge cities. The result shows that the policy is effective from the perspective of environment. However, in the face of complex water ecological environment, there are still some deficiencies in the policy. We therefore put forward policy suggestions for Shenzhen Municipal Government to manage its construction of sponge city in the future.